HUBUNGAN KEMAMPUAN BERPIKIR KREATIF DAN PENGUASAAN KALA DENGAN KETERAMPILAN MENULIS EKSPOSISI BAHASA INGGRIS - Franscy, Franscy (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2017)
The purpose of the research is to finding out correlation between creative thinking ability and English exposition writing skill, the mastering English tenses and English exposition writing skill, and creative thinking ability together with the mastering English tenses towards English exposition writing skill. The used methods for this research were quantitative and survey. The population is students’ eleventh grade. The sample was 30% from the population selected through simple random sampling. To find out the correlation and regression among the variables, EXCEL software was technically used. The findings indicates that there is a positive correlation between creative thinking ability and English exposition writing skill, a positive correlation between the mastering English tenses and English exposition writing skill, and also a positive correlations together between creative thinking ability and the mastering English tenses towards English exposition writing skill.